2002
DOI: 10.1242/jcs.115.3.485
|View full text |Cite
|
Sign up to set email alerts
|

Menadione-induced apoptosis: roles of cytosolic Ca2+elevations and the mitochondrial permeability transition pore

Abstract: In normal pancreatic acinar cells, the oxidant menadione evokes repetitive cytosolic Ca2+ spikes, partial mitochondrial depolarisation,cytochrome c release and apoptosis. The physiological agonists acetylcholine and cholecystokinin also evoke cytosolic Ca2+ spikes but do not depolarise mitochondria and fail to induce apoptosis. Ca2+ spikes induced by low agonist concentrations are confined to the apical secretory pole of the cell by the buffering action of perigranular mitochondria. Menadione prevents mitochon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 145 publications
(18 citation statements)
references
References 57 publications
0
18
0
Order By: Relevance
“…This process increases mitochondrial ROS generation, leading to apoptosis by induction of the mitochondrial permeability transition pore complex. 237 Additionally, mitochondrial dysfunction elicits increased ROS generation in the ER. During glucose starvation in yeast (which activates oxidative phosphorylation that occurs in the mitochondria), inactivation or loss of cytochrome-C oxidase (CCO) of the mitochondrial ETC results in upregulation of ROS generation from the surface of the ER.…”
Section: Chemical Reviewsmentioning
confidence: 99%
“…This process increases mitochondrial ROS generation, leading to apoptosis by induction of the mitochondrial permeability transition pore complex. 237 Additionally, mitochondrial dysfunction elicits increased ROS generation in the ER. During glucose starvation in yeast (which activates oxidative phosphorylation that occurs in the mitochondria), inactivation or loss of cytochrome-C oxidase (CCO) of the mitochondrial ETC results in upregulation of ROS generation from the surface of the ER.…”
Section: Chemical Reviewsmentioning
confidence: 99%
“…Earlier studies showed that the oxidant MD induced apoptosis in certain cells . It was also reported that cell death triggered by MD was independent of the apoptotic pathway .…”
Section: Resultsmentioning
confidence: 99%
“…This event can, in turn, induce redox signaling through the activation of mitochondrial metabolism, further inducing the accumulation of additional H 2 O 2 . This positive feedback mechanism attenuates when Ca 2+ returns from the mitochondrial matrix to the ER [ 66 , 67 ]. This process can be beneficial or detrimental, depending on the cellular context and the levels of ROS generated.…”
Section: Ca 2+ and Oxidative Stressmentioning
confidence: 99%